Complete nucleotide sequence and genome organization of hibiscus chlorotic ringspot virus, a new member of the genus Carmovirus: Evidence for the presence and expression of two novel open reading frames - Huang, M. (2014)
10.1128/JVI.74.7.3149-3155.2000